2001
DOI: 10.1177/154193120104501421
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Upper Limb Loading, Physical Findings, and Discomfort Associated with Keyboard Use

Abstract: This paper presents findings of a preliminary investigation of the relationship between upper limb muscle loading, reported discomfort, and clinical findings associated with keyboard use. Surface electromyography (SEMG) was recorded bilaterally from the digit flexors (FDS), digit extensors (EDC), and m. trapezius of 52 employees of a large insurance company during their normal work activities involving keyboarding.Normalized SEMG amplitude served as a measure of loading on the relevant muscle groups. Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Hagberg and Sundelin (1986) used EMG to reliably correlate muscular load to subjective measures of discomfort, such as Borg scales of perceived exertion, on the upper trapezius muscle for 6 female VDT workers. Lowe, Moore, Swanson, Perez, and Alderson (2001) investigated the relationship between upper limb muscle loading, reported discomfort and keyboard use and found that EMG measures of upper limb loading did not predict MSDs as well as the presence of existing symptoms.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%
“…Hagberg and Sundelin (1986) used EMG to reliably correlate muscular load to subjective measures of discomfort, such as Borg scales of perceived exertion, on the upper trapezius muscle for 6 female VDT workers. Lowe, Moore, Swanson, Perez, and Alderson (2001) investigated the relationship between upper limb muscle loading, reported discomfort and keyboard use and found that EMG measures of upper limb loading did not predict MSDs as well as the presence of existing symptoms.…”
Section: Musculoskeletal Disordersmentioning
confidence: 99%